(untitled) (MAUSAM, 1970)
A budgetary method to appraise the various shortwave attenuation processes in the atmosphere is described, The method is based on observed global and diffuse radiation from sun and sky, given separately for clear days and all days with average cloud cover, New Delhi was selected as a case study because cloudiness, precipitable water, and aerosol content of the air show pronounced annual variations, It is shown that the monsoon period does not produce radical changes in aerosol absorption, More significant is a decrease in the intensity of aerosol scattering. This may be interpreted as a change in particle composition and size distribution, While the monsoon rains remove most of the mineral dust, enough hygroscopic nuclei remain in the air over New Delhi so that attenuation by absorption decreases only slowly after the rains have stopped. The total heating by all absorbers in the atmosphere varies from 0’ 54°C /day in January-March to I, 23°C/day in July-September, Aerosol contributes about 30 per cent to the tOta.1 heating.